A critical analysis of the mechanisms for settlement of investment disputes in international arbitration (2017)
This paper analyses the mechanism for settlement of investment dispute in International Arbitration, The paper adopts doctrinal and analytical approach to legal research. The study examines the provisions of the International Centre for Settlement of Investment Dispute (ICSID) being the most recognised platform for settlement of investment dispute. However, references were made to similar institutions for comparison. The study reveals that Investment Treaties - either multi or bilateral treaty (BITs) are entered into to provide avenue for settlement of investment dispute that nay arise between states or their nationals to the treaty. The paper argues that certain provisions of ICSID and other institutional mechanisms for settlement of investment dispute contain compulsory arbitration thereby negating the concepts of consent and party autonomy which are salient elements of international arbitration. The paper concludes with recommendations that the offending provisions of ICSID should be reformed in tandem with jurisprudence of arbitration proceedings.